Improving the Youth HIV Prevention and Care Cascades: Innovative Designs in the Adolescent Trials Network for HIV/AIDS Interventions - Naar, Sylvie (AIDS Patient Care STDS, 2019)
Dramatic decreases in HIV transmission are achievable with currently available biomedical and behavioral interventions, including antiretroviral therapy and pre-exposure prophylaxis. However, such decreases have not yet been realized among adolescents and young adults. The Adolescent Medicine Trials Network (ATN) for HIV/AIDS interventions is dedicated to research addressing the needs of youth at high risk for HIV acquisition as well as youth living with HIV. This article provides an overview of an array of efficient and effective designs across the translational spectrum that are utilized within the ATN. These designs maximize methodological rigor and real-world applicability of findings while minimizing resource use. Implementation science and cost-effectiveness methods are included. Utilizing protocol examples, we demonstrate the feasibility of such designs to balance rigor and relevance to shorten the science-to-practice gap and improve the youth HIV prevention and care continua.